Relative Role of Eukaryotic and Prokaryotic Microorganisms in Phenanthrene Transformation in Coastal Sediments - MacGillivray, A. Ronald (1994)
The relative role of eukaryotic versus prokaryotic microorganisms in phenanthrene transformation was measured in slurries of coastal sediment by two different approaches: detection of marker metabolites and use of selective inhibitors on phenanthrene biotransformation. Phenanthrene biotransformation was measured by polar metabolite formation and CO(2) evolution from [9-(14)C]phenanthrene. Radiolabeled metabolites were tentatively identified by high-performance liquid chromatography (HPLC) separation combined with UV/visible spectral analysis of HPLC peaks and comparison to authentic standards. Both yeasts and bacteria transformed phenanthrene in slurries of coastal sediment. Two products of phenanthrene oxidation by fungi, phenanthrene trans-3,4-dihydrodiol and 3-phenanthrol, were produced in yeast-inoculated sterile sediment. However, only products of phenanthrene oxidation typical of bacterial transformation, 1-hydroxy-2-naphthoic acid and phenanthrene cis-3,4-dihydrodiol, were isolated from slurries of coastal sediment with natural microbial populations. Phenanthrene trans-dihydrodiols or other products of fungal oxidation of phenanthrene were not detected in the slurry containing a natural microbial population. A predominant role for bacterial transformation of phenanthrene was also suggested from selective inhibitor experiments. Addition of streptomycin to slurries, at a concentration which suppressed bacterial viable counts and rates of [methyl-(3)H]thymidine uptake, completely inhibited phenanthrene transformation. Treatment with colchicine, at a concentration which suppressed yeast viable counts, depressed phenanthrene transformation by 40%, and this was likely due to nontarget inhibition of bacterial activity. The relative contribution of eukaryotic microorganisms to phenanthrene transformation in inoculated sterile sediment was estimated to be less than 3% of the total activity. We conclude that the predominant degraders of phenanthrene in muddy coastal sediments are bacteria and not eukaryotic microorganisms.